2022
DOI: 10.3389/fmicb.2022.960857
|View full text |Cite
|
Sign up to set email alerts
|

Epicuticular wax of sweet sorghum influenced the microbial community and fermentation quality of silage

Abstract: Epicuticular wax, as secondary metabolites (hydrophobic compounds) covering plant surface, plays important roles in protecting plants from abiotic and biotic stresses. However, whether these compounds will influence fermentation process of silage is still not clear. In this study, two sweet sorghum cultivars with varying epicuticular wax on sheath (bloom), Yajin 2 (YJ, less bloom), and Jintian (JT, dense bloom), were harvested at flowering and maturing stages, and ensiled with or without bloom, aiming to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The next stage is the stage of temperature treatment of lignocellulosic biomass to release sugars [30]. There are various approaches for preliminary biomass preparation [31], such as organosolv [32,33], using alkalis [34], diluted acids [35,36], ionic liquids [37][38][39], high-frequency heating [40], treatment with hot steam [41,42], lime [43], or ammonia [44]. Our research focused on the use of the most promising methods and their comparison, namely, pretreatment using organosolv treatment or thermobaric autohydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The next stage is the stage of temperature treatment of lignocellulosic biomass to release sugars [30]. There are various approaches for preliminary biomass preparation [31], such as organosolv [32,33], using alkalis [34], diluted acids [35,36], ionic liquids [37][38][39], high-frequency heating [40], treatment with hot steam [41,42], lime [43], or ammonia [44]. Our research focused on the use of the most promising methods and their comparison, namely, pretreatment using organosolv treatment or thermobaric autohydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, wax loads on stems (13-32 ug/cm 2 ) are >10-fold higher than on leaf blades (0.7-1.5 ug/cm 2 ) ( Suh et al., 2005 ; Lee and Suh, 2015 ). In sorghum, leaf blade wax loads have been reported to vary from 2-25 ug/cm 2 depending on genotype and stage of development ( Nobel and Jordan, 1983 ; McWhorter et al., 1990 ; Burow et al., 2008 ; Burow et al., 2009 ; Xiao et al., 2020 ; Busta et al., 2021 ; Tang et al., 2022 ). Higher wax loads are reported for sorghum leaf sheaths (~36-206 ug/cm 2 ) ( McWhorter et al., 1990 ; Burow et al., 2008 ; Burow et al., 2009 ; Xiao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of sorghum wax chemistry showed that triterpenoids could have an important impact on cuticular transpiration at high temperatures ( Busta et al., 2021 ). Differences in the wax composition of sorghum leaf blades, leaf sheaths, stems and grain has been documented although the functional significance of these differences requires further investigation ( Hwang et al., 2002 ; Harron et al., 2017 ; Xiao et al., 2020 ; Busta et al., 2021 ; Tang et al., 2022 ). The availability of variation in wax load among sorghum accessions and the generation and characterization of sorghum wax mutants ( Peters et al., 2009 ; Xin et al., 2009 ; Xin et al., 2021 ) has enabled QTL, association, and map-based identification of several sorghum genes involved in cuticle and wax biosynthesis ( Burow et al., 2008 ; Burow et al., 2009 ; Awika et al., 2017 ; Punnuri et al., 2017 ; Uttam et al., 2017 ; Elango et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%